Amino Acid Profile, Group of Functional and Molecular Weight Distribution of Goat Skin Gelatin That Produced Through Acid Process (Faculty of Animal Science Universitas Brawijaya, 2011)
Gelatin is a product of hydrolysis of collagen protein from animals that are partially processed.Â Gelatin used in food and non food industries.Â Gelatin is produced when many import of raw skins and bones of pigs and cows.Â Goat skins potential as a raw material substitution that still doubt its halal. Process production of gelatin determine the properties of gelatin. The objectives of this research were to determine amino acid profile, group of functional and molecular weight distribution of gelatin made from goat skins which was produced through a process of acid. The skin of male Bligon goat, 1.5 to 2.5 year old was used as raw materials. Process production of gelatin was using acid type acetic acid (CH3COOH 0.5 M) (v/v) as curing material. The experimental design applied in this study and commercial gelatin was used as control. The results showed that gelatin produced from goat skin through the process of acid had properties identical with commercial gelatin. It can be concluded that the gelatin has the potential substitute product of commercial gelatin. Keywords: collagen, gelatin, goat skin, curing, acid process